Inter‐ and intraobserver agreement in whole‐slide digital ThinPrep samples of low‐grade squamous lesions of the cervix uteri with known high‐risk HPV status: A multicentric international study. Issue 12 (14th July 2022) - Kholová, Ivana; Negri, Giovanni; Nasioutziki, Maria; Ventura, Laura; Capitanio, Arrigo; Bongiovanni, Massimo; Cross, Paul A.; Bourgain, Claire; Edvardsson, Henrik; Granados, Rosario; Lipiński, Artur; Obermann, Ellen Christina; et al.
Abstract : Background: High‐risk human papilloma virus (HR HPV) testing and liquid‐based cytology are used for primary cervical screening. Digital cytology, based on whole‐slide scanned samples, is a promising technique for teaching and diagnostic purposes. The aim of our study was to evaluate the interobserver and intraobserver variation in low‐grade squamous lesions, HR HPV status bias, and the use of whole‐slide scanned digital cervical cytology slides. Methods: Fifteen expert cytopathologists evaluated 71 digitalized ThinPrep slides (31 atypical squamous cells of undetermined significance [ASC‐US], 21 negative for intraepithelial lesion or malignancy, and 19 low‐grade squamous intraepithelial lesion cases). HR HPV data were accessible only in the second round. Results: In interobserver analysis, Kendall's coefficient of concordance was 0.52 in the first round and 0.58 in the second round. Fleiss' kappa values were 0.29 in the first round and 0.31 in the second round. In the ASC‐US category, Fleiss kappa increased from 0.19 to 0.22 in the second round and the increase was even higher expressed by Kendall's coefficient: from 0.42 to 0.52. In intraobserver analysis, personal scores were higher in the second round. Conclusions: The interobserver and intraobserver variability in low‐grade squamous lesions was within fair agreement values in the present study, in line with previous works. The comparison of two rounds showed that expert cytopathologists are generally unbiased by the knowledge of HR HPV data, but that being informed of the HR HPV status leads to a better agreement. Stain quality and back discomfort were highlighted as factors affecting digital cytopathology use. Abstract : The interobserver and intraobserver variability in low‐grade squamous lesions was within fair agreement values and knowing high‐risk human papillomavirus status leads to better agreement. Stain quality and back discomfort were highlighted as factors affecting digital cytopathology use.